REALISASI PEMBAYARAN PAJAK RESTORAN DIMASA PANDEMI COVID-19 DI KOTA BANJARMASIN - Nisfi Yulida; Rusma Nailiah (Universitas Lambung Mangkurat, 2022)
This study aims to find out how the realization of restaurant tax payments during the covid-19 pandemic in the city of Banjarmasin. The results of this study indicate that restaurant tax revenues at the Regional Revenue and Asset Financial Management Agency decreased in 2020, because it was the peak of the covid-19 pandemic which had an impact on the number of restaurant visitors decreasing due to the decline in the community's economy. It can be seen that the pandemic has affected the realization of restaurant tax payments in the city of Banjarmasin.